Pain Management on Elderly People: Caregivers Readiness on Managing Pain at Home - Kartika, Imelda Rahmayunia; Sa'adiah, Halimahtun; Febrina, Wiwit (REAL in Nursing Journal, 2024)
Background: The diseases that appear in the elderly tend to create excessive and chronic pain with the prevalence of pain occurs in people over 65 years of age. Families as caregivers have to pay more attention to the condition of the elderly so that they need readiness and skills on managing pain at home. Caring on the elderly was very complex and requires patience, including in pain treatment. This study was to overview the family readiness on managing pain for the elderly people.Methods: This study used an analytic descriptive design with a sample of 98 caregivers who cared for the elderly with pain at home. The research instrument used the Nursing Outcomes Classification on a 5-likert scale which asked about family readiness in caring for the family. Data analyzed by using descriptive frequency analysis.Results: A total of 53 people (54.1%) caregivers stated that they were not prepared to care for elderly people with pain at home. It was explained that caregivers mostly stated that they did not know about the disease process of elderly pain and the recommended treatment procedures on managing the pain (each mean of 1.923 and 2.000). Meanwhile, caregivers generally accepted the condition as taking on the role of home care (mean: 3.317).Conclusion: It was concluded that caregivers tended to not have the readiness in taking care of elderly pain at home. It is expected that caregivers can increase knowledge about pain management and be ready to provide home care to the elderly.Keywords: Pain management, caregivers, readiness, elderly, home